Motor learning and control concepts and applications - Magill, Richard A.; Anderson, David I. (New York McGraw Hill, 2021)
This twelfth edition primarily updates the previous edition by adding more recent research and interpretations of the concepts and theoretical views associated with those concepts that were in the eleventh edition. Similar to the previous editions this new edition continues its two most distinctive features as an introductory motor learning and control textbook: its overall approach to the study of motor learning and control and the organization of the implementation of that approach. In every edition of this book, the overall approach has been the presentation of motor learning and control "concepts" to identify the common theme of each chapter
1. The classification of motor skills -- 2. The measurement of motor performance -- 3. Motor abilities -- 4. Neuromotor basis for motor control -- 5. Motor control theories -- 6. Sensory components of motor control -- 7. Performance and motor control characteristics of functional skills -- 8. Action preparation -- 9. Attention as a limited capacity resource -- 10. Memory components, forgetting, and strategies -- 11. Defining and assessing learning -- 12. The stages of learning -- 13. Transfer of learning -- 14. Demonstration and verbal instruction -- 15. Augmented feedback -- 16. Practice variability and specificity -- 17. The amount and distribution of practice -- 18. Whole and part practice -- 19. Mental practice
"This international student edition is for use of outside of the U.S." - book cover
Includes bibliographical references and indexes
Keywords: Motor learning -- Textbooks